Torsion design of lightweight concrete beams without or with fibers: A comparative study and a refined cracking torque formula. (December 2020) - Deifalla, A.
Abstract: Although a well established comprehension of the torsional design is a must for an accurate and economic design of concrete members, however, after 180 years of research very little is known about the torsion design of lightweight concrete (LWC) beams. Several projects are undergoing with the objective of improving design provisions, including but not limited to those for shear, torsion, and LWC, however, very limited studies have tackled either torsion design or combined torsion, shear and flexure design of LWC beams. This current study examines the current design of LWC beams under torsion. Selected torsion design provisions were reviewed and outlined. Findings from previous experimental testing of LWC beams under torsion were reviewed and outlined. An experimental database was compiled from previous works available in the literature, with a total of 90 beams tested under significant torsion. The cracking and ultimate torsion strength of all tested beams were calculated using selected design codes. The calculated cracking and ultimate torsion strength were compared to the experimentally observed ones. The effect of various parameters on the safety, accuracy, and consistency of the torsion design of LWC beams using various design codes was investigated. Cracking torque needed a revisit in order to account for LWC and using fibers in the concrete mix. A new formula for cracking torsional moments, which included the effect of all effective parameters was developed, validated, and proposed. The proposed formula was found to be remarkably better than existing design codes. More experimental testing for LWC beams under combined loading is needed in order to refine existing design codes and proposed formula.